Astrocytes from the brain microenvironment alter migration and morphology of metastatic breast cancer cells. Issue 11 (9th August 2017) - Shumakovich, Marina A.; Mencio, Caitlin P.; Siglin, Jonathan S.; Moriarty, Rebecca A.; Geller, Herbert M.; Stroka, Kimberly M.
Abstract : Tumor cell metastasis to the brain involves cell migration through biochemically and physically complex microenvironments at the blood‐brain barrier (BBB). The current understanding of tumor cell migration across the BBB is limited. We hypothesize that an interplay between biochemical cues and physical cues at the BBB affects the mechanisms of brain metastasis. We found that astrocyte conditioned medium(ACM) applied directly to tumor cells increased tumor cell velocity, induced elongation, and promoted actin stress fiber organization. Notably, treatment of the extracellular matrix with ACM led to even more significant increases in tumor cell velocity in comparison with ACM treatment of cells directly. Furthermore, inhibiting matrix metalloproteinases in ACM reversed ACM's effect on tumor cells. The effects of ACM on tumor cell morphology and migration also depended on astrocytes' activation state. Finally, using a microfluidic device, we found that the effects of ACM were abrogated in confinement. Overall, our work demonstrates that astrocyte‐secreted factors alter migration and morphology of metastatic breast tumor cells, and this effect depends on the cells' mechanical microenvironment.—Shumakovich, M. A., Mencio, C. P., Siglin, J. S., Moriarty, R. A., Geller, H. M., Stroka, K. M. Astrocytes from the brain microenvironment alter migration and morphology of metastatic breast cancer cells. FASEB J. 31, 5049–5067 (2017). www.fasebj.org